Intrauterine Pressure Catheter in Labor: Associated Microbiology. Issue 1 (1993) - Pinell, Phillip; Faro, Sebastian; Roberts, Scott; Le, Sy; Maccato, Maurizio; Hammill, Hunter
Abstract : Objective: The purpose of this study was to determine if bacterial growth occurred in the amniotic fluid of laboring women. Twenty patients who required an intrauterine pressure catheter (IUPC) during labor were studied. Amniotic fluid samples were aspirated during labor and at the time of delivery. Methods: IUPCs were placed in laboring patients for a variety of reasons. Cervical cultures were taken prior to insertion of an IUPC. After the IUPC was placed, amniotic fluid cultures were taken both at the time of placement and 30 minutes prior to delivery. These cultures were sent for aerobic, anaerobic, Mycoplasma, and Ureaplasma cultures. Results: The increase in bacterial concentration from the initial sample to the final sample was statistically significant ( P < 0.01) for both aerobes and anaerobes. Amniotic fluid samples demonstrated a median of 0 bacterial species per patient on initial collection and 2 bacterial species per patient in final collection. The mean count of cfu for erobes in the initial amniotic samples was 3.5 ×10 4, compared to that of the second samples, which was 1.4 ×10 5 . The mean count of cfu for anaerobes in the initial amniotic fluid samples, .was 4.1 ×10 2, compared to that of the second samples, which was 8.0 ×10 3 . Only 3 of 20 patients developed chorioamnionitis, with only 1 patient having an increased number ofbacterial species significantly higher than the median. Although 80% of patients had a colony count ≥10 2 cfu/cc, only 19% of this group developed chorioamnionitis. Conclusions: The number of bacterial species and colony counts increased significantly during labor, but this factor alone was not enough to cause chorioamnionitis in a significant number of patients.